Chile : Request for an Arrangement Under the Flexible Credit Line-Press Release; Staff Report; and Staff Supplement. (IMF Staff Country Reports; Country Report ;, 2020)
This paper explores Chile's Request for an Arrangement Under the Flexible Credit Line (FCL). Chile qualifies for the FCL by virtue of its very strong fundamentals, institutional policy frameworks, track record of economic performance and policy implementation and commitment to maintain such policies in the future. Notwithstanding its very strong fundamentals and policy settings, Chile's open economy is exposed to substantial external risks as a result of the ongoing coronavirus disease 2019 outbreak, including a significant deterioration in global demand for Chilean exports, a sharp decline or reversal of capital inflows toward emerging markets, and an abrupt tightening of global financial conditions. The authorities intend to treat the FCL arrangement as precautionary and temporary, and to exit the arrangement as soon as the 24-month period is completed, conditional on a reduction of risks at the time of the mid-term review.